PENGEMBANGAN PROGRAM GERAKAN LITERASI SEKOLAH DI SD NEGERI 02 BATU MANGAUM KEC. SUNGAI GERINGGING KABUPATEN PADANG PARIAMAN - Sabir, Arisman; Triza, Retno; Fitria, Desi (Jurnal Pengabdian Pendidikan Masyarakat (JPPM), 2023)
The objectives of this service include: 1) Growing student awareness through increasing teacher creativity about the importance of literacy skills in increasing knowledge to become active, creative, innovative, and independent students. 2) Reading corners, bulletin boards, and visits to the library can increase students' interest in reading if they are designed in an attractive way. The method used is lecture and discussion. This training was attended by 20 teachers from various subject areas in the school. The development of the School Literacy Movement Program was carried out based on several stages including; consists of three stages, namely planning, implementing and evaluating. The resource person plans the learning to be carried out, such as preparing learning tools and media in the form of power points, pictures and videos about GLS which are applied to increase the literacy of teachers and students. Then another teacher as an observer (observer). In the implementation stage, the teacher and observers evaluate the implementation of activities in class. This activity adds to the knowledge of teachers and students about the School Literacy Movement and gains new experiences for teachers, so as to increase the creativity of educators and students.